2021
DOI: 10.36660/ijcs.20200102
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Cardiac Enzymes and Cardiotrophin-1 Levels in Patients with Acute Coronary Syndrome

Abstract: Cardiovascular diseases are the major causes of mortality and morbidity, especially among the aging population. 1 Studies have reported that one out of every five deaths in the United States is caused by coronary atherosclerosis. 2 It is expected that CAD will take the number 1 place in the list of 2020 causes of death prepared by the World Health Organization 3 Similar studies examining coronary artery disease (CAD) associated mortality in European countries (an average of 30 countries) report that the aforem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…A clinical study by M. O. Matokhniuk et al has revealed a correlation between plasma CT and LV myocardial mass index in the patients with heart failure [19]. The same result presented study by U. Polat et al can be used as a new biomarker and correlated with standard markers of myocardial ischemia [20]. This may have led to the decrease in ejection fraction in rats after prolonged hypoxia.…”
Section: Original Researchmentioning
confidence: 59%
“…A clinical study by M. O. Matokhniuk et al has revealed a correlation between plasma CT and LV myocardial mass index in the patients with heart failure [19]. The same result presented study by U. Polat et al can be used as a new biomarker and correlated with standard markers of myocardial ischemia [20]. This may have led to the decrease in ejection fraction in rats after prolonged hypoxia.…”
Section: Original Researchmentioning
confidence: 59%